A review on possible approaches of anaerobic biological processes for palm oil mill effluent: Process, quality, advantages, and limitations - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus (IOP Publishing, 2020)
Palm oil mills play an essential role in the economic development of many countries. Though, it is the primary source of environmental pollution and degradation. Water scarcity and the high cost of new water supply technologies are the two major factors responsible for the increasing recognition of the importance to conserve water resources by wastewater treatment and reuse. Sustainability of sanitation systems should be related to low requirements in cost, energy consumption, and maintenance. Anaerobic biotreatment is the preferred industrial choice for mediating high strength wastewater. Anaerobic biotreatments for wastewater are increasingly being researched as cost-effective alternatives to deliver low sludge accumulation, efficient biodegradation and mineralisation, microbes' reduction, and solids-free effluents. In the last decade, many studies investigated various types of anaerobic reactors in combination with membranes. This review shows the potential of anaerobic bio mediations for palm oil mill effluent. Also, the paper discusses the impact of various factors on both biological and filtration performances and identifying strengths and limitations.